Chemical Properties and Characteristics of Cow Milk Yogurt with Different Additional Fruit and Storage Time - Wulansari, Putri Dian; Kusmayadi, Andri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
This research was aimed to evaluate the composition (total solids, water content, fat and protein), qualitative properties (color, aroma, and texture) and quantitative properties (free fatty acid and lactic acid) of cow milk yogurt with different fruits addition and storage time. Experimental method applied Completely Randomized Design with five treatments namely control, dragon fruit, mango, apple and banana (20% v/v), each with 5 replicates. Qualitative characteristic assessment was conducted on 0, 5, 10 and 15 days of storage. Result showed that fruit addition significantly affected the composition and characteristics, while storage time significantly affected quantitative characteristics of yogurt. Apple and banana increased 13% total solids of plain yogurt, while the highest fat content (4,516%) was observed in control yogurt which had the lowest protein content (2,564). The highest free fatty acidÂ was in control yogurt ripen for 15 days (22,885%) while the lowest free fatty acid was in mango yogurt ripen for 10 days (13,915%). Fruit addition in yogurt ripen for 15 days at 5C resulted in a safe consumed product.Â